AB0202 Changes and significance of dendritic cells in peripheral blood in patients with systemic lupus erythematosus. (23rd January 2014) - Wang, G.; Zhao, X.; Yu, D.; Li, X.; Li, X.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by immunological intolerance, hyperactivity of various immunocyte and production of a variety of autoantibodies. Although etiology of the disease remains unclear, there is an increasing evidence that the presence and accumulation of dendritic cells in target tissues may play a role in the pathogenesis of SLE. Objectives: To explore the changes and significance of plasmacytoid dendritic cells (PDC), myeloid dendritic cells (MDC) and cytokines in peripheral blood in patients with SLE. Methods: The propotions of PDC and MDC in peripheral blood from 38 SLE and 15 normal individuals were measured by flowcytometer. The concentrations of IFN-α, TNF-α and IL- 6 were detected using ELISA. Results: 1. The levels of PDC and MDC in peripheral blood of SLE patients decreased significantly comparing with normal controls (P<0.01). 2. It was found that the percentage of PDC in SLE patients with stable disease was significantly higher than patient with active disease (P<0.05). No significant difference was found in MDC between patients with and without disease activity. 3. SLE patients with proteinuria had lower percentage of PDC comparing with patients without proteinuria (P<0.05). In addition, anti-dsDNA negative patients had higher percentage of PDC than anti-dsDNA positive patients (P<0.05). 4. The percentage of PDC was correlated significantly with SLEDAI, C3 and ESR (with r value of -0.363, 0.451, -0.453 and p value of 0.031, 0.001, 0.008 respectively). 5. Further study found SLE patients had higher level of IFN-α, IL-6 and TNF-α than controls (P<0.05). No correlation was found between the percentage of PDC, MDC and level of IFN-α, IL-6 and TNF-α. Conclusions: The percentages of PDC and MDC in peripheral blood are decreased in patients with SLE. The reduction of PDC is correlated with disease activity and kidney damage of SLE. Disclosure of Interest: None Declared